The Evolution of Regulation of Compulsory Licence in International and Serbian Sources of Patent Law - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In this paper the author gives an overview of the regulation of compulsory licence in international and Serbian sources of patent law. From international sources the subjects of analysis are the Paris Convention, TRIPS Agreement and the Community Patent Convention, whereby the last one has not come into force yet, but also contains rules on compulsory license. As far as Serbian law is concerned, all patent laws are analysed, from the first one adopted as early as 1922 in the first Yugoslavia, until the effective Patent Law from 2011. The evolution of compulsory licence is traditionally paralleled to the institution of forfeiture of patent. As the forfeiture of patent, as a sanction against the patent owner who does not intend to exploit the invention, was gradually losing its significance, so were the rules on compulsory licence becoming more detailed and nuanced. Nevertheless, at present compulsory licence is an instrument rarely applied in practice. This is primarily true of cases of compulsory licences that are usually referred to as classical, such as the one issued when the patent holder does not exploit the invention or exploits it insufficiently and the one issued for the purpose of exploitation of a dependent patent, on the one hand, and the compulsory licence issued in public interest in narrower sense, on the other. It is to be expected, however, that two latest subcategories of compulsory licence, the one issued as a remedy for the infringement of the rules of competition and the one issued for the production of medicines for the purpose of export into countries with problems relating to public health, will be applied more frequently in practice.